PERLINDUNGAN HUKUM BAGI KREDITUR ATAS SAHAM TANPA WARKAT (SCRIPLESS) SEBAGAI OBJEK JAMINAN GADAI - Fathira Tri Waladi; S Susiana (Jurnal Geuthèë: Penelitian Multidisiplin, 2022)
Scripless shares are one of the objects of collateral as regulated in article 60 section (2) of UUPT. Collateral provides guarantee for repayment of debts to creditors as regulated in article 1150 of the Indonesian civil code. Yet, scripless shares collateral is different from general collateral, where the object of collateral is not on the creditor, and the value of shares changes anytime.  This study aims to explain the legal protection for the creditor on scripless shares collateral. Based on findings, the author found that the current regulations have not yet provided maximum legal protection for the creditor in the scripless shares collateral system. KSEI only acts as the depositor of the collateral object and not obliged to guarantee the fulfillment of the creditor’s rights. Thus, when the blocking of collateral shares is lifted, KSEI does not have to ensure that the rights of creditors have been fulfilled. Based on the findings, the author suggests a regulation that obliges KSEI to ensure the creditor’s rights have been fulfilled to be made, before unblocking the collateral objects.